2021
DOI: 10.4028/www.scientific.net/ssp.314.237
|View full text |Cite
|
Sign up to set email alerts
|

Contact Vs. Non-Contact Cleaning: Correlating Interfacial Reaction Mechanisms to Processing Methodologies for Enhanced FEOL/BEOL Post-CMP Cleaning

Abstract: Due to the emergence of sub-7 nm technologies, next generation CMP slurry formulations have continued to increase in additive (nanoparticle and chemistry) complexity to meet stringent device specifications. Therefore, it is essential to probe the molecular level interactions at the nanoparticle/slurry chemistry/substrate interface and in turn correlate them to key performance metrics such as removal rate, post CMP defects, and planarization efficiency. This work will address key interactions through a series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In previous work, the use of megasonic cleaning coupled with supramolecular structures has been reported as an effective way remove CeO 2 from TEOS surfaces at significantly reduced shear force (20). This case study evaluates the megasonic processing condition (i.e., pulsed wave) to assess the cleaning efficiency in a system with increased cavitation compared to a constant megasonic wave.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, the use of megasonic cleaning coupled with supramolecular structures has been reported as an effective way remove CeO 2 from TEOS surfaces at significantly reduced shear force (20). This case study evaluates the megasonic processing condition (i.e., pulsed wave) to assess the cleaning efficiency in a system with increased cavitation compared to a constant megasonic wave.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve better cleaning performance, different types of physical cleaning methods (of contact and non-contact types) are applied in the post-CMP cleaning. One promising candidate of non-contact cleaning methods is based on megasonic water flow of nozzle injection type [1]; recent studies suggest that cavitation bubbles in water flow under megasonic wave irradiation play a key role in particle removal [2,3,4]. However, megasonic cleaning with acoustic cavitation is known to have a side effect, giving rise to surface damage due to violent bubble collapse.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that the shape and charge of the supramolecular structure play a crucial role in effective CeO 2 nanoparticle removal. 19 21 More specifically, upon delivery to the wafer surface, micelles recover at a slower rate than polyelectrolytes. Though these additives do reduce the overall shear force and help to minimize defectivity induced during the cleaning process, it is not perfect and can cause p-CMP defects from the contact modality.…”
Section: Introductionmentioning
confidence: 99%
“…While this has shown to be an effective mode of particle removal, there is an increase in the process shear force (mechanical component), which results in secondary defect formation (i.e., increased scratching/surface roughness). , More recently attention has shifted to developing p-CMP cleaning formulations that employ encapsulation of the CeO 2 nanoparticle using supramolecular chemistries (i.e., surfactants, polyelectrolytes, liposomes, etc.). Previous work has shown that the shape and charge of the supramolecular structure play a crucial role in effective CeO 2 nanoparticle removal. More specifically, upon delivery to the wafer surface, micelles recover at a slower rate than polyelectrolytes. Though these additives do reduce the overall shear force and help to minimize defectivity induced during the cleaning process, it is not perfect and can cause p-CMP defects from the contact modality.…”
Section: Introductionmentioning
confidence: 99%